2012
DOI: 10.1186/cc11652
|View full text |Cite
|
Sign up to set email alerts
|

The pediatric sepsis biomarker risk model

Abstract: IntroductionThe intrinsic heterogeneity of clinical septic shock is a major challenge. For clinical trials, individual patient management, and quality improvement efforts, it is unclear which patients are least likely to survive and thus benefit from alternative treatment approaches. A robust risk stratification tool would greatly aid decision-making. The objective of our study was to derive and test a multi-biomarker-based risk model to predict outcome in pediatric septic shock.MethodsTwelve candidate serum p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
200
0
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 179 publications
(214 citation statements)
references
References 29 publications
1
200
0
8
Order By: Relevance
“…However, these studies used International Classification of Diseases, Ninth Revision (ICD-9), codes, which have been shown to capture a lower severity of illness and thereby underestimate mortality (5,7). In a recent database study using expanded ICD-9 coding, researchers reported a PICU mortality of 26.4% (6), and authors of prospective studies have reported short-term mortality rates up to 24% (2,5,19,46,47). The mortality in the present study also reflects the high rate of multiorgan dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…However, these studies used International Classification of Diseases, Ninth Revision (ICD-9), codes, which have been shown to capture a lower severity of illness and thereby underestimate mortality (5,7). In a recent database study using expanded ICD-9 coding, researchers reported a PICU mortality of 26.4% (6), and authors of prospective studies have reported short-term mortality rates up to 24% (2,5,19,46,47). The mortality in the present study also reflects the high rate of multiorgan dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Пошук чутливих маркерів ССЗР і сепсису залиша-ється актуальним питанням [23]. За даними аналітичних оглядів, за останні роки було вивчено більше ніж 178 біомаркерів сепсису [24][25][26].…”
Section: (89)2017 інфекційні хворобиunclassified
“…А з іншого боку, його розглядають в якості перспективного маркера септичного процесу. Підвищення його рівня спостеріга-ється у хворих дітей з бактеріологічно підтвердженим сепсисом і септичною енцефалопатією [23].…”
Section: (89)2017 інфекційні хворобиunclassified
See 2 more Smart Citations